2020
DOI: 10.1111/dpr.12428
|View full text |Cite
|
Sign up to set email alerts
|

Linking sanitation policy to service delivery in Rwanda and Uganda: From words to action

Abstract: Motivation The gap between policy, implementation and outcome is neither new nor specific to the sphere of sanitation. This article attempts to apply policy implementation literature in the context of developing countries, when much of the scholarly work on implementation and policy process and empirical research has been in the context of developed countries. Purpose This article explores the gap between sanitation policy intentions and outcomes in a comparative study in Rwanda and Uganda with “good” and “lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Water governance is also constrained by policies involving significant compromises-and the political will/capacity to address these may be lacking. Some of these include urban water supply governance (Adams et al, 2019), sanitation governance (Ekane et al, 2014(Ekane et al, , 2020, irrigation governance (Lefore et al, 2019;Woodhouse et al, 2017), groundwater governance (Jiménez et al, 2017;Whaley et al, 2019), community water supply governance (Alexander et al, 2015), governance of water related disasters (Bahta et al, 2016;Bottazzi et al, 2019;King-Okumu et al, 2018). The multiple dimensions of water governance suggest a need to adopt a polycentric approach to water governance considering the interlinkages among the different dimensions.…”
Section: Water Governancementioning
confidence: 99%
“…Water governance is also constrained by policies involving significant compromises-and the political will/capacity to address these may be lacking. Some of these include urban water supply governance (Adams et al, 2019), sanitation governance (Ekane et al, 2014(Ekane et al, , 2020, irrigation governance (Lefore et al, 2019;Woodhouse et al, 2017), groundwater governance (Jiménez et al, 2017;Whaley et al, 2019), community water supply governance (Alexander et al, 2015), governance of water related disasters (Bahta et al, 2016;Bottazzi et al, 2019;King-Okumu et al, 2018). The multiple dimensions of water governance suggest a need to adopt a polycentric approach to water governance considering the interlinkages among the different dimensions.…”
Section: Water Governancementioning
confidence: 99%
“…Subnational governance plays a key role in enabling access to improved sanitation, by enhancing or limiting the effectiveness of national sanitation policies . Huston et al found that district-level bodies were an effective platform for learning and knowledge dissemination and that actors at this level were representative of key roles and perspectives related to water governance .…”
Section: Methodsmentioning
confidence: 99%
“…The diverse approaches used in these four countries may provide insight on how to eliminate OD and increase Basic sanitation under the SDGs. The sanitation strategies documented in other countries with high OD may also provide insight, for example Haiti [46,47] and Rwanda [48,49]. Ghana provides an example of an approach based on shared sanitation that could yield progress on preventing disease, even though it may not contribute substantially to global sanitation targets.…”
Section: Plos Watermentioning
confidence: 99%